To ask, or not to ask: the hesitation process described by district nurses encountering women exposed to intimate partner violence. Issue 15 (30th September 2015) - Sundborg, Eva; Törnkvist, Lena; Saleh‐Stattin, Nouha; Wändell, Per; Hylander, Ingrid
Abstract : Aims and objectives: To improve the understanding of district nurses' experiences of encountering women exposed to intimate partner violence. Background: Intimate partner violence is a public health issue that influences all aspects of affected women's lives; it is thus of great relevance to identify intimate partner violence. District nurses in primary health care in Sweden encounter women of all ages and are therefore in a unique position to identify intimate partner violence and provide nursing care. However, studies indicate that several barriers have kept nurses from identifying intimate partner violence. Consequently deeper understanding of district nurses' encounters with women exposed to intimate partner violence is needed. Design: A qualitative study using grounded theory method. Methods: Interviews with 11 district nurses in primary health care in Sweden. Results: The hesitation process is central in these encounters. Several barriers to asking and factors that facilitated asking impacted the hesitation process. Under the influence of these factors, district nurses moved from being unaware that identifying intimate partner violence was their professional responsibility, to becoming ambivalent about asking, to starting to prepare themselves to ask about intimate partner violence. The presence of factors that facilitated asking finally made district nurses feel prepared, and then they decided to ask women about intimate partner violence. Conclusions: The concept of managing the hesitation process could be used to be incorporated in continuing education and training. Barriers and facilitators concerning organisational factors found in this study may be specific to the Swedish health care system, but the concept of the hesitation process is applicable in similar contexts and perhaps to other issues about which it is difficult to ask. Relevance to clinical practice: This study illuminates the importance of a supportive work environment in reducing district nurses' hesitation to ask about intimate partner violence and to propose continuing education, training and supervision for district nurses regarding intimate partner violence.